Analisis Faktor Lingkungan Fisik Sebagai Determinan Transmisi Infeksi Nosokomial Di Rumah Sakit: Tinjauan Sistematis - Intan Sekar Arumdani; Dwi Fitriani (Unit Penelitian & Pengabdian Masyarakat STIKes Adi Husada, 2026)
Background: Healthcare-associated infections (HAIs) constitute a significant global health challenge, exacerbating morbidity, mortality, and economic burdens. The hospital environment encompassing air quality, water systems, surface contamination, and building design serves as a potential pathogen reservoir and a primary transmission pathway. With HAI prevalence ranging from 3.0% to 20.7% and incidence rates between 5% and 10%, Aims: this study aims to synthesize scientific evidence from observational studies regarding the influence of environmental factors on the incidence of nosocomial infections.. Methods: This systematic review was conducted in adherence to the PRISMA guidelines. A comprehensive literature search was performed across ScienceDirect, ProQuest, JSTOR, Scopus, Sinta, PubMed, Google Scholar, and Portal Garuda databases. The inclusion criteria prioritized observational studies addressing environmental factors and HAIs. Study quality was evaluated using relevant critical appraisal instruments, followed by a qualitative synthesis of the data. Results: Thirteen articles met the inclusion criteria. The synthesis indicates that poor air quality, high levels of surface contamination, unmanaged water systems, and suboptimal ward design are significantly correlated with an increased risk of nosocomial infections. Conclusion: Environmental factors are critical determinants in the transmission of infections within hospital settings. The implementation of strict disinfection protocols, improvements in ventilation systems, and facility designs grounded in infection prevention principles are paramount to enhancing patient safety and ensuring cost-efficiency in healthcare.